A Survey on Livestock Health Care Delivery System in Maharashtra of India - Aithal, H P; Das, S K; Bhilegaonkar, K N (International Journal of Environment, Agriculture and Biotechnology, 2023)
Feedback of 250 Livestock Development Officers (LDO) of Maharashtra state was taken regarding the livestock health care delivery system in pre constructed format. The study revealed that 17.60 % LDO were looking after five and more than five dispensaries and23.20 % LDO were taking care of livestock from more than 20 villages. Many of the LDOs (56.80 %) were also involved in different extension works such as implementation of Gov. Schemes, survey work and cattle show etc., besides treatment of animals. Majority of the officers (72.40 %) visited farmer’s house as and when farmers called. Moreover, 69.60 % LDO informed that they visited village for the treatment of livestock very often.Most of the officers informed about sufficient stock of vaccine (82.00 %), antibiotic (60.00 %), anthelmentis and analgesics (63.60 %), but 42.00 % LDO reported scarcity of vitamin and mineral mixture.In respect of disease outbreak / occurrence, LDO reported outbreak of 22 diseases in livestock and poultry. Most occurrence of disease was FMD in cattle (28.00 %), followed by PPR in goat (24.80 %) and HS in cattle (14.40%). 31.20 % respondents reported more than two weeks time was needed to get diagnostic report of disease from the testing laboratory.32.80 % LDO informed that they reported to the District Animal Husbandry Officer regarding outbreak / occurrence of disease.The officers revealed that the regular vaccination was carried out against FMD (97.20 %),HS (93.20 %) and BQ (92.00 %). 35.60 % respondents reported vaccine failure and cause of vaccine failure was found to be improper storage and transportation of vaccine (17.20 %) followed by untimely vaccination (10.80 %) and some even doubted about the quality of vaccine. 47.60 % LDO reported the sufficient availability of acaricide and 67.20 % respondents informed sufficient availability of anthelmintic in the animal health center.Artificial Insemination was preferred over natural service by farmers for breeding of livestock as reported by 83.60 % respondents.Conception rate in AI was reported to be 45.27 %, whereas number of AI / conception was reported to be 2.85. Reason for preference of AI by most of the farmers was easy availability (46.00 %) followed by better conception rate (43.60%).